“A life with no fixed points” the subaltern deconstructing normative linearities - GONÇALVES, Davi Silva (Grau Zero – Revista de Crítica Cultural, 2016)
According to Spivak (2000, p. 21) more thannecessary translation is inevitable, even if it is still considered impossible. When translation takes place, the “I” gets in touch with the “Other” and this “Other” is, as posed by Maggio (2007, p. 424), (re)created through what the author calls a “reductionist postmodernity”. Therefore, this article aims at rethinking Latin American postmodernity, more specifically in the Amazonian region, through the problematisation of time and space as defined by the (neo)imperial narratology. Such problematisation is here effected through Hatoum’s novel The Brothers (2002), translated by John Gledson, which potentialises this criticismby inserting into the hegemonic centre the voice of a margin that, for so long, has been silenced by it.